Peningkatan Aktivitas Belajar Siswa dalam Pembelajaran IPA melalui Lesson Study - Jelita Jelita; Yenny Suzana; Nuraida Nuraida (JIPI (Jurnal IPA dan Pembelajaran IPA), 2020)
Lesson study is an activity carried out collaboratively by teachers in planning a creative, effective and communicative learning process so that the desired learning objectives can be achieved. Student learning activities in learning science are observed using a scientific approach that is the ability of students to observe objects, submit questions, gather information, associate and communicate learning materials. The purpose of this study is to determined the increase in student learning activities in science learning through lesson study in MIN 3 Langsa and MIN 2 Aceh Tamiang. This type of research is a qualitative descriptive. The sample of this study consisted of 60 fifth grade students from 30 MIN 3 Langsa students and 30 MIN 2 Aceh Tamiang students. The sampling technique used by purposive sampling technique. Data was collected through observation sheets totaling 15 items consisting of 5 indicators of learning activities. Data were analyzed by comparing the average score of each item with the maximum score using the percentage formula. The results showed an increase in student learning activities in science learning in both Madrasah Ibtidaiyah namely 32.98% MIN 2 Aceh Tamiang and 42.16% MIN 3 Langsa. Thus it can be concluded that student learning activities in science learning can be improved through lesson study